Відділ археології ранніх слов’ян (до 30-річчя наукової діяльності) - Баран, В.Д.; Абашина, Н.C. (Археологія, 2005)
Статтю присвячено відділу археології ранніх слов’ян — одному з визнаних наукових центрів дослідження проблем походження та історії слов’ян переддержавного періоду, з часу заснування якого нещодавно минуло 30 років. В статье, подготовленной к 30-летию со дня основания отдела археологии ранних славян, рассмотрены наиболее важные вехи становления отечественной археологической славистики. Значительное внимание уделено проблематике научных исследований сотрудников отдела. Приведена краткая характеристика их экспедиционных работ. Дана оценка научным результатам, полученным учеными отдела в изучении проблемы происхождения и ранней истории славян. The article prepared to the 30th anniversary of establishment of Early Slavs Archaeology Department considers the most important milestones of formations of domestic archaeological Slavonic studies. Considerable attention is paid to the subjects of research activities of the staff. A brief description of their field work is presented. Scientific research results obtained by the scholars of the department in the study of the problem of origin and early history of the Slavs are estimated.